Deciphering paleoclimate sensitivity across time and space - Kaboth-Bahr, Stefanie (Dr.) (2021)
This habilitation thesis includes seven case studies that examine climate variability during the past 3.5 million years from different temporal and spatial perspectives. The main geographical focus is on the climatic events of the of the African and Asian monsoonal system, the North Atlantic as well as the Arctic Ocean. The results of this study are based on marine and terrestrial climate archives obtained by sedimentological and geochemical methods, and subsequently analyzed by various statistical methods. The results herein presented results provide a picture of the climatic background conditions of past cold and warm periods, the sensitivity of past climatic climate phases in relation to changes in the atmospheric carbon dioxide content, and the tight linkage between the low and high latitude climate system. Based on the results, it is concluded that a warm background climate state strongly influenced and/or partially reversed the linear relationships between individual climate processes that are valid today. Also, the driving force of the low latitudes for climate variability of the high latitudes is emphasized in the present work, which is contrary to the conventional view that the global climate change of the past 3.5 million years was predominantly controlled by the high latitude climate variability. Furthermore, it is found that on long geologic time scales (>1000 years to millions of years), solar irradiance variability due to changes in the Earth-Sun-Moon System may have increased the sensitivity of low and high latitudes to Influenced changes in atmospheric carbon dioxide. Taken together, these findings provide new insights into the sensitivity of past climate phases and provide new background conditions for numerical models, that predict future climate change. Die vorliegende Habilitationsschrift umfasst sieben Fallstudien, die die Klimavariabilität während der letzten 3,5 Millionen Jahre aus verschiedenen zeitlichen und räumlichen Perspektiven behandeln. Dabei liegt das geographische ...